Credible, incredible: the miraculous in the ancient Mediterranean : the majority of the essays in this collection were written for a Conference "Glaubwürdig oder Unglaubwürdig? Erzählung und Rezeption wunderbarer Ereignisse in der Antiken Welt" held at the University of Regensburg in June 2011 - Nicklas, Tobias; Spittler, Janet E. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2013)
In this collection of essays, the product of a symposium held at the University of Regensburg in June 2011, scholars of the ancient Mediterranean explore the representation of miracles in ancient literature. The following key questions are addressed: How do ancient authors express their attitude toward the miracles they report? What value do they place in miraculous accounts? How do they qualify, cast doubt on, or deny the validity of a report? What are the relationships between the various literary genres and religious contexts within which miraculous stories are told? The contribution of this volume lies in the juxtaposition of various perspectives: Jewish, Christian and pagan authors are all brought into play; texts in which accounts of miracles are narrated are discussed alongside texts in which authors reflect on such accounts - either positively or negatively. Contributors:
Keywords: Mediterranean Region -- History -- To 476 -- Congresses; Konferenzschrift; Konferenzschrift -- 2011 -- regensburg; Frühchristentum; Frühjudentum; Wunder; Antike; Römisches Reich; Griechenland